A flow cytometric method of ligand binding to isolated receptors using micro beads - (:unkn) unknown (MEDIMOND S R L, 2003)
There are various methods in measuring the ligand binding to receptors. A quantitative flow cytometric method of described for binding measurements of FITC labelled ligands to receptor coated micro beads. GpIIb/IIIa complex was purified from human platelets by affinity chromatography and coated to polystyrene micro beads. Fibrinogen (Fg) was labelled with FITC. Different concentrations of Fg-FITC with GpIIb/IIIa coated micro beads were incubated and analyzed by flow cytometry. BSA-FITC was used as a negative control. The Fg-FITC binding to isolated platelets was also studied under the same conditions. This method besides showing quantitative ligand binding to the receptor, it also reflects the in vivo binding conditions.
Keywords: FIBRINOGEN BINDING; ACTIVATED PLATELETS; WHOLE-BLOOD; AGGREGATION; EXPRESSION; IIIA